2021
DOI: 10.24093/awej/covid.14
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Practices in Instructor E-feedback: A Case Study of E-feedback given in Three Linguistic Courses during the COVID 19 Pandemic

Abstract: This study aimed to investigate the instructor’s electronic feedback practices during the COVID 19 Pandemic in terms of the nature of the content of e-feedback, the formulation, the challenges, and the multimodal nature of the instructor’s e-feedback. This study used a qualitative case study to obtain data from the instructor’s e-feedback in three linguistic courses as delivered, practiced by the single English language instructor. The instructor’s e-feedback via Blackboard and WhatsApp platform and the follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This indicates that Saudi students find revisions based on local feedback much easier than global feedback and as feedback providers, they are more likely to notice and provide feedback on local issues than global ones. This could be due to the context of the study and has also been confirmed by others (Alnasser & Alyuosef, 2015; O AbuSa’aleek & Shariq, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…This indicates that Saudi students find revisions based on local feedback much easier than global feedback and as feedback providers, they are more likely to notice and provide feedback on local issues than global ones. This could be due to the context of the study and has also been confirmed by others (Alnasser & Alyuosef, 2015; O AbuSa’aleek & Shariq, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…• the effects of the pandemic on education, teachers, students, resources, and policies (Atmojo & Nugroho, 2020;Dhawan, 2020;Donitsa-Schmidt & Ramot, 2020;Haslam et al, 2020;Kerres, 2020;König et al, 2020;Octaberlina & Muslimin, 2020;Rapanta et al, 2020;Rinekso & Muslim, 2020;Schultz & DeMers, 2020;Son et al, 2020;Şendoğan Erdoğan, 2020;Taşçı, 2021) • students' writing skills during the pandemic (AbuSa'aleek & Shariq, 2021;Bin Dahmash, 2020;Öztürk Karataş & Tuncer, 2020;Yamashita, 2021; Zhang & Chen, 2021) • the impact of peer feedback on students' writing, autonomy, and self-evaluation (Hyland, 2000;Rollinson, 2005;Villamil & De Guerrero, 1996) • the importance of peer feedback training (Can, 2019;Min, 2005Min, , 2006Rahimi, 2013;Subaşı, 2002) • effectiveness of computer-mediated writing instruction and anonymous peer feedback (Alharbi, 2018;Alhujaylan, 2019;Blake & Delforge, 2006;DiGiovanni & Nagaswami, 2001;Jiang & Yu, 2014;Lee, 2005;Liaw, 1998;Liu & Sadler, 2003;Razı, 2016;Tanaka, 2015;Tatsanajamsuk & Saengboon, 2011;Zaini & Mazdayasna, 2014)<...…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, along with reporting the high percentage of positive experiences with BB, Al-Khresheh (2021) also mentioned several issues that could slow down the adoption of this tool. Such issues, as argued by AbuSa’aleek and Shariq (2021) , can include students’ preference issues, technical issues, and timing issues, among others.…”
Section: Literature Reviewmentioning
confidence: 99%